The green alga Dictyosphaerium chlorelloides biomass and polysaccharides production determined using cultivation in crossed gradients of temperature and light - Kumar, Dhanesh; Kvíderová, Jana; Kaštánek, Petr; Lukavský, Jaromír (Engineering in life sciences, 2017)
The green microalga Dictyosphaerium chlorelloides was identified as promising microorganism for biotechnological production of exopolysaccharides (EPS). In stationary phase the culture suspension solidifies to thick gel, with very high viscosity and high content of EPS which may be interesting for many biotechnological applications. To develop cultivation protocol for maximum biomass/polysaccharide production, the optimum conditions for growth and polysaccharides production were determined in this study using the crossed gradient cultivation method. Temperature and irradiance requirements of Dictyosphaerium chlorelloides were evaluated by statistical analyses for growth rate/biomass, extracellular (EPS) and intracellular (IPS) polysaccharides contents in crossed gradients of temperature (4-45°C) and irradiance (2-18 W/m2, 9.1 - 82.3 μmol/(m2 s)). The maximum relative growth rate was observed at temperatures around 19.2°C and relatively low irradiances in range 2.6-11 W/m2 (11.9-50.3 μmol/(m2 s)). The maximum IPS production was observed at temperatures around 19.2°C and irradiance around 11 W/m2 (50.3 μmol/(m2 s)). The maximum production of EPS was observed at temperatures around 25.7°C and similar irradiances as IPS production. Due to temperature separation of growth and EPS production, development of cultivation protocol based controlled temperature manipulation is possible.
Keywords: Crossed gradients; Irradiance; Biomass; Polysaccharides; Temperature